Effect of regional alpha- and beta-adrenergic blockade on blood flow in the resting forearm during contralateral isometric handgrip. - Eklund, B (1976)
In a previous study we have shown that an isometric handgrip is accompanied by a rapid decrease in vascular resistance in the resting (contralateral) forearm, lasting for about 1 min, which in all probability is neurogenic. 2. In the present study the distribution of the vasodilatation was investigated by analysing O2 saturation in a deep vein, draining mainly muscle tissue. Some possible neurogenic mechanisms for the vasodilatation were tested by repeating the handgrip after local beta- and alpha-adrenergic blockade of the resting forearm with propranolol and phentolamine, respectively. 3. Without blockades the forearm vascular resistance decreased and the deep vein O2 saturation increase to similar degrees on contralateral handgrip. Propranolol markedly reduced both the decrease in resistance and the increase in deep vein O2 saturation. Phentolamine did not alter the initial decrease in resistance, but with phentolamine resistance continued to decrease after 1 min. 4. It is concluded that the rapid decrease in vascular resistance in the resting forearm on contralateral handgrip takes place, to a great extent, in muscle. It is mediated by neurogenic beta-adrenergic mechanisms and if the contraction is prolonged it gradually changes to a vasoconstriction mediated by alpha-adrenergic mechanisms.